Efficient localization of a native metal ion within a protein by Cu2+-based EPR distance measurements. Issue 20 (8th February 2019) - Gamble Jarvi, Austin; Cunningham, Timothy F.; Saxena, Sunil
Abstract : A native paramagnetic metal binding site in a protein is located with less than 2 Å resolution by a combination of double histidine (dHis) based Cu 2+ labeling and long range distance measurements by EPR. Abstract : Electron paramagnetic resonance (EPR) based distance measurements have been exploited to measure protein–protein docking, protein–DNA interactions, substrate binding and metal coordination sites. Here, we use EPR to locate a native paramagnetic metal binding site in a protein with less than 2 Å resolution. We employ a rigid Cu 2+ binding motif, the double histidine (dHis) motif, in conjunction with double electron electron resonance (DEER) spectroscopy. Specifically, we utilize a multilateration approach to elucidate the native Cu 2+ binding site in the immunoglobulin binding domain of protein G. Notably, multilateration performed with the dHis motif required only the minimum number of four distance constraints, whereas comparable studies using flexible nitroxide-based spin labels require many more for similar precision. This methodology demonstrates a significant increase in the efficiency of structural determinations via EPR distance measurements using the dHis motif.